Does Exposure to Counterstereotypical Role Models Influence Girls’ and Women’s Gender Stereotypes and Career Choices? A Review of Social Psychological Research - Olsson, Maria; Martiny, Sarah E. (Frontiers in Psychology, 2018)
Gender roles are formed in early childhood and continue to influence behavior through adolescence and adulthood, including the choice of academic majors and careers. In many countries, men are underrepresented in communal roles in health care, elementary education, and domestic functions (HEED fields, Croft, Schmader, & Block, 2015), whereas women are underrepresented in the science, technology, engineering, and mathematical (STEM) fields (Beede et al., 2011) and top leadership positions (Leopold, Ratcheva, & Zahidi, 2016). Theories focusing on the development of gender roles suggest that across the lifespan people perceive certain roles to be more or less appropriate for their gender (e.g., Gender Schema Theory, Martin & Halverson, 1981; Social Role Theory, Eagly & Wood, 2011). Specifically, researchers have postulated that observing same-sex role models triggers learning processes whereby observers internalize gender-stereotypical knowledge of roles and act accordingly, which results in gender-congruent aspirations and behavior. It seems reasonable that if observing men and women in gender congruent roles fosters gender-congruent aspirations and behavior, then frequently observing gender-incongruent role models (e.g., male kindergarten teachers or female scientists and leaders) should reduce gender stereotyping and promote gender-counterstereotypical aspirations and behavior. In many countries, governments and societal decision-makers have formed initiatives based on the idea that exposure to gender-counterstereotypical role models influences aspirations and career choices among children, adolescents, and young adults. The present review gives an overview of research-based interventions involving observing or interacting with counterstereotypical role models, particularly focusing on outcomes for girls and women. Extending earlier reviews, we summarize laboratory-based and field-based studies and then critically discuss and integrate the findings in order to provide an overall picture of how counterstereotypical role models shape observers’ occupational aspirations and academic choices in childhood, adolescence, and young adulthood. We conclude by outlining suggestions for future research and briefly discussing implications for future interventions.